2002
DOI: 10.1159/000065317
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Transfusion

Abstract: Despite recent advances in blood screening techniques, transfusions are not risk-free procedures. Screening for viral and bacterial infections as well as other newly emerging agents continues to attract attention in the medical and health policy communities. At the same time, as healthcare costs rise and available financial resources are limited, governments and other decisionmaking bodies increasingly require cost-effectiveness analyses to justify (or reject) allocation of those limited resources to new techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In a recent review, Yeh et al . [62] identified 14 articles, published between 1993 and 2000, that examined commonly employed blood safety interventions. The median value for these measures was $500 000 per QALY gained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review, Yeh et al . [62] identified 14 articles, published between 1993 and 2000, that examined commonly employed blood safety interventions. The median value for these measures was $500 000 per QALY gained.…”
Section: Discussionmentioning
confidence: 99%
“…This might explain why a variety of interventions related to blood safety have been adopted despite evidence of high cost per unit health effect (Table 7). In a recent review, Yeh et al [62] identified 14 articles, published between 1993 and 2000, that examined commonly employed blood safety interventions. The median value for these measures was $500 000 per QALY gained.…”
Section: Discussionmentioning
confidence: 99%
“…For example, for transplantation services, relatively high thresholds for cost‐effectiveness are implicitly applied with transplantations of the liver and the lung costing approximately €100 000 per discounted LYG (Michel et al ., 1994; Al et al ., 1998). Also for transfusion safety, relatively high net costs per discounted LYG – up to one million €'s – seem to be accepted in the Netherlands and other countries (Postma, Staginnus et al ., 2001; Van Hulst et al ., 2002; Yeh et al ., 2002). For example, we recently estimated cost‐effectiveness of NAT of Dutch donors for HIV at €200 000 to over one million €'s (Postma et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Next to the ‘maximum‐safety’ criterion, cost‐effectiveness is becoming an important issue in judging new technologies, also in blood transfusion. Relatively high cost‐effectiveness ratios are seemingly accepted in the blood transfusion area (Van Hulst et al ., 2002; Yeh et al ., 2002). For example, at estimated current Dutch levels of risk for HIV transmission through transfusion, HIV NAT costs several millions per life‐year gained (LYG) (Postma et al ., 2001).…”
mentioning
confidence: 99%
“…Another component of transfusion costs are the various blood safety techniques used to purify, conserve, or screen blood. 91 A recent study that reviewed the literature on the costeffectiveness of such technologies found that most were more than $200,000/quality-adjusted life year (QALY) or life-year saved. Fewer than 35% had cost-effectiveness ratios below $50,000/QALY, a value generally accepted as a threshold for an intervention having an acceptable cost.…”
Section: Cost Considerations Of Anemia Management Practices In the Inmentioning
confidence: 99%